More than meets the eye : seeing art with all five senses - Raczka, Bob (Millbrook Press, 2003)
Provides images of paintings and new, sensory ways to experience them, such as tasting the milk in Vermeer's "The Milkmaid," hearing the music in Tanner's "The Banjo Lesson," or feeling the fur in da Vinci's "Lady with an Ermine."